Patriotism in Javed Manzar's Poetry - Andleeb, Fatima; Rehman, Muhammad; Shah, Mutahir (sourcecoder, 2022)
Javed Manzar is a poet of civilized expression. He started his Poetic Journey when he was a schoolboy of 13 years. As his Poetic career progressed, his poetry took a new dimension towards maturity of mind and simplicity in style. There is a novelty in his thoughts and simplicity in his diction. All these qualities are a source of enhancing the impact of his poetry. The freshness of ideas, the eloquence in expression, the distinctive style of communication, all go together to make him the Poetic of unique style and Diction.His poetry depicts the love for motherland,which needs no justification. He takes pride in having Urdu as his mother tongue and national language‘’.